Collins COBUILD advanced dictionary of American English (Boston, MA : Thomson ELT/Harper Collins, 2007)
Contents: Dictionary text A-Z -- Brief grammar reference -- Brief writer's handbook -- Brief speaker's handbook -- Text messaging and emoticons -- Defining vocabulary -- Academic word list -- Geographical places and nationalities.
Keywords: English language -- Dictionaries